Measurement of the branching fraction ratio RK at large dilepton invariant mass - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
A test of lepton universality between muons and electrons is performed using B+ → K+ℓ+ℓ− decays (where ℓ = e, μ), in the dilepton invariant-mass-squared region above 14.3 GeV2/c4. The data used for the measurement consists of beauty meson decays produced in proton-proton collisions, corresponding to an integrated luminosity of 9 fb−1, collected by the LHCb experiment between 2011 and 2018. The ratio of branching fractions for B+ → K+μ+μ− and B+ → K+e+e− decays is measured to be $$ R_K=1.0{8}_{-0.09}^{+0.11}{\left(stat\right)}_{-0.04}^{+0.04}\left(syst\right) $$, which is consistent with the Standard Model prediction of unity. This constitutes the most precise test of lepton flavour universality using B+ → K+ℓ+ℓ− decays with dilepton invariant-mass-squared above the ψ(2S) mass, whilst being the first of its kind at a hadron collider.
Veröffentlicht: 17. Juli 2025
*The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, M.D. Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, Y. Zhao, A. Zhelezov [und sehr viele weitere Personen]
Im Titel ist die Buchstabe "K" tiefgestellt
Gesehen am 02.02.2026